Analisis Potensi Bahaya Kecelakan Kerja Menggunakan Hazard and Operability Study di PT.XYZ (UNISTEK, 2022)
PT.XYZ is one of the manufacturing companies engaged in paper and tissue products in Indonesia. Since the establishment of this company, there have been many problems with occupational health and safety. In identifying Occupational Health and Safety (K3) at institutions and projects, there are several methods that can be used, one of which is Hazard and Operability Studies (HAZOP). HAZOP is a standard hazard analysis technique used in the preparation of safety determinations in new or modified systems for the presence of a potential hazard or problem. Based on research that has been carried out using the Hazard and Operability Study method, 9 sources of danger are obtained, where the extreme risk that can cause work accidents is sourced from the attitude of the workers themselves and the temperature in the room. The use of PPE and providing K3 scheduling regarding the use of PPE is very important to avoid the risk of work accidents and improve health and safety while working is quite important in the production area of PT.XYZ